Gambierdiscus cf. yasumotoi (Dinophyceae) isolated from New Zealand's sub‐tropical northern coastal waters - L Rhodes; G Giménez Papiol; K Smith; T Harwood (New Zealand Journal of Marine and Freshwater Research, 2014)
A globular form of the epiphytic dinoflagellate genus, Gambierdiscus , was isolated and cultured from Northland, New Zealand. The closest species, based on Bayesian analyses of the large subunit ribosomal DNA (LSU rDNA) D1‐D3 and D8‐D10 regions, were G. yasumotoi and G. ruetzleri . The thecal plate morphology of the isolate, in particular the small pores and large 2’’’’ plate, most closely resembled G. yasumotoi . However, the ratios of the cell measurements (depth‐to‐width 1.3 and length‐to‐width 1.4) were more similar to G. ruetzleri and suggest that morphological variability exists within the globular Gambierdiscus group. The isolate produced putative maitotoxin‐3, but no maitotoxin‐1 or ciguatoxin.